Wound-type electrode assembly and lithium secondary battery including same

The wound-type electrode assembly with strategically aligned carbon-based negative electrode layers addresses the issue of current collector deterioration in lithium secondary batteries, achieving uniform charging performance and extended battery life.

JP2025501196AActive Publication Date: 2025-01-17LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024539355
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2023-09-15
Publication Date
2025-01-17
Estimated Expiration
2043-09-15

AI Technical Summary

Technical Problem

Conventional lithium secondary batteries with graphite-oriented negative electrodes experience performance deterioration due to wrinkling, unraveling, and buckling of the negative electrode current collector during long-term charging and discharging, leading to non-uniform lithium ion movement and reduced charging performance.

Method used

A wound-type electrode assembly is designed with a negative electrode having carbon-based negative electrode active layers on both sides of the current collector, where the first layer is farther from the winding center, and the alignment of the carbon-based negative electrode active material is controlled through magnetic field application, ensuring a higher degree of alignment for the first layer and a lower degree for the second layer, using specific alignment ratios and angles to optimize lithium ion movement.

Benefits of technology

The solution enhances uniform charging performance and reduces performance deterioration of the negative electrode current collector, extending the lifespan and improving long-term charging and discharging capabilities of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501196000001_ABST
    Figure 2025501196000001_ABST
Patent Text Reader

Abstract

The present invention relates to a wound-type electrode assembly and a lithium secondary battery including the same. The wound-type electrode assembly can realize uniform charging performance of the electrode assembly by controlling the degree of alignment of a carbon-based negative electrode active material contained in a negative electrode active layer according to the degree of separation of the negative electrode active layer provided on both sides of a negative electrode current collector with respect to the winding center of the electrode assembly. The wound-type electrode assembly can also improve performance degradation caused by wrinkles, unraveling, buckling, etc. of the negative electrode current collector during long-term charging and discharging, and thus a secondary battery including the same has excellent long-term charging and discharging performance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0116882 dated September 16, 2022 and Korean Patent Application No. 10-2023-0104698 dated August 10, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a wound-type electrode assembly and a lithium secondary battery including the same. [Background technology]

[0003] 2. Description of the Related Art In recent years, secondary batteries have been widely used not only in small devices such as portable electronic devices, but also in medium- to large-sized devices such as battery packs for hybrid and electric vehicles and power storage devices.

[0004] In a lithium secondary battery, charging and discharging are performed by the movement of lithium ions between a positive electrode and a negative electrode. Such lithium secondary batteries can be manufactured in various forms. For example, there is a structure including an electrode body in the form of a rolled-up sheet electrode (i.e., a roll-up electrode assembly).

[0005] Specifically, the wound electrode assembly is formed, for example, by spirally winding a negative electrode sheet having a structure in which a negative electrode active material layer containing a negative electrode active material is supported on both sides of a negative electrode current collector, and a positive electrode sheet having a structure in which a positive electrode active material layer containing a positive electrode active material is supported on both sides of a positive electrode current collector, with a separator sheet interposed therebetween.

[0006] Here, the negative electrode 13 of the wound electrode body 10 may have negative electrode active layers 13b and 13c on both sides of the negative electrode current collector 13a, as shown in FIG. 1. In this case, the second negative electrode active layer 13b located on the inside with respect to the winding center of the electrode body 10 as the reference has a larger area ratio than the adjacent first positive electrode active layer 11ac, and the first negative electrode active layer 13c located on the outside with respect to the winding center of the electrode body as the reference has a smaller area ratio than the adjacent second positive electrode active layer 11bb. As a result, the first negative electrode active layer 13c has a larger area ratio than the adjacent second positive electrode active layer 11bb, and ...b has a larger area ratio than the adjacent first positive electrode active layer 11bb. nd The kinetics of lithium ions moving from the first positive electrode active layer 11ac to the second negative electrode active layer 13b (1 st kinetics), the end of charge time is shortened as compared to the first negative electrode active layer 13c.

[0007] That is, even in the case of a negative electrode active layer provided on one negative electrode, the area ratio of the negative electrode active layer to the adjacent positive electrode active layer varies depending on the position, and a difference in the lithium ion migration speed occurs between the negative electrode active layer and the positive electrode active layer. This difference in the lithium ion migration speed causes poor charging performance of the negative electrode active layer located on the outer side based on the negative electrode current collector.

[0008] On the other hand, examples of the negative electrode active material used in the negative electrode include graphite materials such as natural graphite. Such graphite has a layered structure, and is formed by stacking many layers in which carbon atoms form a network structure and spread out in a planar shape. Lithium ions penetrate into the edge surfaces (surfaces where layers overlap) of such graphite layers during charging of the secondary battery and diffuse between the layers. In addition, lithium ions can be desorbed and released from the edge surfaces of the graphite layers during discharge. In addition, since the electrical resistivity of the graphite layers in the planar direction is lower than that in the stacking direction of the graphite layers, a detouring electron conduction path is formed along the planar direction of the layers.

[0009] In this regard, a technique has been proposed for magnetically orienting the graphite contained in the negative electrode in order to improve the charging performance of a wound-type electrode assembly in a conventional lithium secondary battery using graphite. Specifically, a magnetic field is applied during the formation of the active layer of the negative electrode to orient the (002) crystal plane of the graphite so that it is inclined almost horizontally with respect to the negative electrode current collector, and then fixed in place. In this case, the edge face of the graphite layer faces the positive electrode active layer, so that lithium ions can be smoothly inserted and removed, and at the same time, the conduction path of electrons can be shortened. This improves the electronic conductivity of the negative electrode, thereby improving the charging performance of a secondary battery including it.

[0010] However, in a wound electrode body having graphite oriented by a magnetic field, repeated charging and discharging over a long period of time causes the negative electrode current collector to wrinkle, unravel, buckle, etc. Such deformation of the negative electrode current collector not only reduces the durability of the negative electrode itself, but also has a limit in inducing performance degradation of the negative electrode active layer disposed on the negative electrode current collector. Summary of the Invention [Problem to be solved by the invention]

[0011] An object of the present invention is to provide a wound-type electrode assembly which induces the orientation of graphite contained in a negative electrode, and which not only has excellent charging performance but also reduces performance degradation caused by deformation of the negative electrode current collector, such as wrinkling, unraveling, and buckling, during long-term charging and discharging, and a lithium secondary battery including the same. [Means for solving the problem]

[0012] In order to solve the above-mentioned problems, in one embodiment, the present invention comprises: A winding-type electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the negative electrode includes a negative electrode current collector, and a first negative electrode active layer and a second negative electrode active layer formed on both sides of the negative electrode current collector, the first negative electrode active layer being located farther away from a winding center of the electrode assembly than the second negative electrode active layer; The first negative electrode active layer has an alignment degree (S 60 / 0 ) is the degree of alignment (S 60 / 0 ) is smaller than the diameter of the wound electrode assembly.

[0013] [Formula 1] S 60 / 0 =I60 B / A / I0 B / A

[0014] [Formula 2] I60 B / A =I60 B / I60 A

[0015] [Formula 3] I0 B / A =I0 B / I0 A

[0016] In formulas 1 to 3, S 60 / 0 is the peak intensity ratio (I0 B / A ) when the X-ray incidence angle is 60° (I60 B / A ) value, I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.

[0017] At this time, the first negative electrode active layer has an alignment degree (OI 1st ) is the alignment degree (OI 2nd ) can be smaller.

[0018] [Formula 4] OI=I 004 / I 110

[0019] In the above formula 4, I 004 represents the area integral value of the peak representing the (004) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer, I 110 represents the area integral value of the peak indicating the (110) crystal plane in X-ray diffraction (XRD) spectroscopic analysis of the negative electrode active layer.

[0020] Specifically, the degree of alignment (OI) of the first negative electrode active layer 1st ) is 0.1 to 2.0, and the degree of alignment (OI) of the second negative electrode active layer is 2nd ) is the degree of alignment (OI) of the first negative electrode active layer 1st ) may have a ratio of 101% to 150%.

[0021] In addition, the first negative electrode active layer has an alignment degree (OI) at the outermost surface of the electrode assembly. 1st ) is the alignment degree (OI 1st ) may have a ratio of 101% to 150%.

[0022] In addition, the first negative electrode active layer has a ratio (I 004 / I 002 ) may be 0.04 or greater.

[0023] The first negative electrode active layer and the second negative electrode active layer each had a thickness of 250 mg / 25 cm 2 ~500mg / 25cm 2 The loading amount may be 0.01 to 0.01.

[0024] Meanwhile, the carbon-based negative electrode active material may include at least one of natural graphite and artificial graphite, and may have a sphericity of 0.75 or more.

[0025] In addition, the positive electrode included in the electrode assembly may include a positive electrode active layer provided on both sides of a positive electrode current collector and including one or more positive electrode active materials selected from lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2.

[0026] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2

[0027] [Chemical formula 2] LiM 2 p Mn 1-p O4

[0028] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more of the elements W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are 1.0≦x≦1.30, 0.5≦y<1, 0 <z≦0.3、0<w≦0.3、0≦v≦0.1であり、かつy+z+w+v=1であり、 M 2 is Ni, Co or Fe, p is in the range of 0.05≦p≦1.0.

[0029] As an example, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O 2、 LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, LiNi 0.7 Mn 1.3 O4, LiNi 0.5 Mn 1.5 O4, and LiNi 0.3 Mn 1.7 It may contain one or more of O4.

[0030] Further, in one embodiment, the present invention provides There is provided a lithium secondary battery including the above-described wound-type electrode assembly according to the present invention. Effect of the Invention

[0031] The wound electrode assembly according to the present invention can realize uniform charging performance of the electrode assembly by controlling the alignment degree of the carbon-based negative active material contained in the negative active layer according to the degree of separation of the negative active layer provided on both sides of the negative current collector with respect to the winding center of the electrode assembly. Furthermore, the electrode assembly can improve performance degradation caused by wrinkles, loosening, buckling, etc. of the negative current collector during long-term charging and discharging, so that a secondary battery including the electrode assembly has excellent long-term charging and discharging performance and life characteristics. [Brief description of the drawings]

[0032] [Figure 1] 1 is a cross-sectional view showing a structure of a winding-type electrode assembly according to the present invention. [Diagram 2] 1 is a cross-sectional view showing a structure of a winding-type electrode assembly according to the present invention. [Diagram 3]13 is an image showing the alignment of the ab-axis crystal planes of graphite depending on whether or not a magnetic field is applied to a negative electrode slurry during the formation of a negative electrode active layer, where (a) shows the case where no magnetic field is applied and the graphite crystal planes are not aligned, and (b) shows the case where a magnetic field is applied and the graphite crystal planes are aligned. [Figure 4] This is an image showing the tendency of the type and position of each orbital absorption peak depending on the angle of incidence of X-rays during near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. (a) shows the type and position of the orbital that forms the double bond of graphite, and (b) shows the peak shape of each orbital position when X-rays are incident. [Diagram 5] 1 is an image showing an incident angle of X-rays during Near Edge X-ray Absorption Fine Structure (NEXAFS) spectroscopy analysis of a negative electrode manufactured according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] Since the present invention can be modified in various ways and can have various embodiments, specific embodiments are described in detail in the detailed description.

[0034] However, this is not intended to limit the invention to any particular embodiment, but it should be understood to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.

[0035] In the present invention, terms such as "comprise" and "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and may be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0036] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "on" can include not only the case where it is located at the top, but also the case where it is located at the bottom.

[0037] In the present invention, "containing as a main component" may mean containing 50% by weight or more (or 50% by volume or more), 60% by weight or more (or 60% by volume or more), 70% by weight or more (or 70% by volume or more), 80% by weight or more (or 80% by volume or more), 90% by weight or more (or 90% by volume or more), or 95% by weight or more (or 95% by volume or more) of a defined component relative to the total weight (or total volume). For example, "containing graphite as a main component as a negative electrode active material" may mean containing 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more of graphite relative to the total weight of the negative electrode active material, and in some cases, it may mean that the entire negative electrode active material is made of graphite and contains 100% by weight of graphite.

[0038] In the present invention, the term "cross-sectional structure" refers to a structure of a surface cut perpendicular to the winding direction of the wound electrode assembly. In this case, the cut surface may be the same as a surface cut parallel to a process direction during the manufacture of the negative electrode, or a surface cut in the longitudinal direction of the negative electrode slurry applied to form the negative electrode active layer. In addition, the cross-sectional structure may include a surface cut in the thickness direction of the wound negative electrode active layer, and may include the winding center and the outermost shell of the negative electrode active layer.

[0039] In addition, in this specification, "the carbon-based negative electrode active material is oriented" or "the carbon-based negative electrode active material is aligned" means that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material constituting the negative electrode active material particles is arranged to have a specific inclination based on the surface of the negative electrode current collector, which may be different from the particles of the carbon-based negative electrode active material themselves being arranged to have a specific direction inside the negative electrode active layer.

[0040] In addition, "high orientation of the carbon-based negative electrode active material" may mean that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer has a high frequency of having a certain inclination with respect to the surface of the negative electrode current collector. In some cases, it may mean that the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle (e.g., an angle close to vertical, more than 45°, specifically 60° or more) with respect to the surface of the negative electrode current collector.

[0041] In addition, "high degree of alignment of carbon-based negative electrode active material" may mean that the "degree of alignment (OI)" referred to in this specification is large, and a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a low angle (e.g., less than 45°) with respect to the surface of the negative electrode current collector. Conversely, "low degree of alignment of carbon-based negative electrode active material" may mean that the "degree of alignment (OI)" is small, and the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle (e.g., an angle close to vertical, 45° or more, specifically 60° or more) with respect to the surface of the negative electrode current collector.

[0042] The present invention will now be described in more detail.

[0043] <Wound-type electrode assembly for lithium secondary batteries> In one embodiment, the present invention comprises: A wound electrode assembly including a positive electrode, a negative electrode, and a separator disposed therebetween, the negative electrode includes a negative electrode current collector, and a first negative electrode active layer and a second negative electrode active layer formed on both sides of the negative electrode current collector, the first negative electrode active layer being located farther away from a winding center of the electrode assembly than the second negative electrode active layer; The first negative electrode active layer has an alignment degree (S 60 / 0 ) is the degree of alignment (S 60 / 0 ) is smaller than the diameter of the wound electrode assembly.

[0044] [Formula 1] S 60 / 0 =I60 B / A / I0 B / A

[0045] [Formula 2] I60 B / A =I60 B / I60 A

[0046] [Formula 3] I0 B / A =I0 B / I0 A

[0047] In formulas 1 to 3, S 60 / 0 is the peak intensity ratio (I0 B / A ) when the X-ray incidence angle is 60° (I60 B / A ) value, I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 Arepresents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.

[0048] The wound-type electrode assembly according to the present invention can be formed by preparing a positive electrode, a negative electrode, and a separator, each of which has a sheet shape, disposing the separator between the positive electrode and the negative electrode, and then winding them up.

[0049] In this case, the negative electrode includes a negative electrode active layer including a carbon-based negative electrode active material on both sides of a negative electrode current collector. The negative electrode active layer refers to a layer that realizes the electrical activity of the negative electrode. The negative electrode active layer includes a carbon-based negative electrode active material as a negative electrode active material to realize electrical activity through a reversible oxidation-reduction reaction during charging and discharging of the battery. Specifically, the carbon-based negative electrode active material means a material mainly composed of carbon atoms, and such a carbon-based negative electrode active material may include graphite. The graphite may include at least one of natural graphite and artificial graphite. For example, the carbon-based negative electrode active material may include natural graphite or artificial graphite alone, or may include a mixture of natural graphite and artificial graphite in some cases. In this case, the mixture ratio of natural graphite and artificial graphite may be 5 to 40:60 to 95, or 10 to 30:70 to 90, based on weight. The carbon-based negative electrode active material contains natural graphite and artificial graphite in the above-mentioned mixing ratio, and thus can realize high orientation of the carbon-based negative electrode active material on the surface of the negative electrode current collector while strengthening adhesion between the negative electrode current collector and the negative electrode active layer.

[0050] The carbon-based negative electrode active material is preferably a spherical graphite granule formed by the aggregation of a plurality of flake graphite. Examples of flake graphite include natural graphite, artificial graphite, mesophase calcined carbon (bulk mesophase) made from tar and pitch, graphitized cokes (raw coke, green coke, pitch coke, needle coke, petroleum coke, etc.), etc. In particular, a graphite granule assembled from a plurality of natural graphites having high crystallinity is preferable. Also, one graphite granule may be formed by the aggregation of 2 to 100 flake graphite particles, preferably 3 to 20 flake graphite particles.

[0051] Such a carbon-based negative electrode active material, specifically, graphite, may have a spherical particle shape, and the sphericity of the graphite particles may be 0.75 or more, for example, 0.75 to 1.0, 0.75 to 0.95, 0.8 to 0.95, or 0.90 to 0.99. Here, the "sphericity" may refer to the ratio of the shortest diameter (minor axis) to the longest diameter (major axis) among any diameters passing through the center of the particle, and when the sphericity is 1, it means that the particle shape is spherical. The sphericity may be measured using a particle shape analyzer, or may be determined by measuring the shape of the particles using a scanning electron microscope (SEM) or an energy dispersive spectrometer, and then analyzing the measurement results.

[0052] The present invention has the advantages of improving the capacity of a battery by realizing a nearly spherical shape of a carbon-based negative electrode active material, thereby realizing high electrical conductivity of a negative electrode active layer, and improving adhesion between a negative electrode active layer and a current collector by increasing a specific surface area of ​​the negative electrode active material.

[0053] In addition, the carbon-based negative electrode active material has an average particle size (D 50 ), specifically, the average particle size (D 50 ) can be shown.

[0054] The average particle size of the carbon-based negative electrode active material is close to a sphere, and it is advantageous to make the particle size smaller in order to maximize the degree of disorder in the direction of expansion of each particle so as to prevent the particle from expanding due to charging with lithium ions. However, if the particle size of the carbon-based negative electrode active material is less than 0.5 μm, a large amount of binder is required due to the increase in the number of particles per unit volume, and the sphericity and sphericity yield may be reduced. On the other hand, if the maximum particle size exceeds 10 μm, the expansion rate of the negative electrode active material during charging and discharging of the secondary battery increases significantly, and the binding between the particles of the negative electrode active material and between the negative electrode active material particles and the current collector decreases due to repeated charging and discharging, and the cycle characteristics may be significantly reduced.

[0055] The negative electrode active layer including such a carbon-based negative electrode active material is disposed on both sides of the negative electrode current collector, and the orientation and / or alignment degree of the carbon-based negative electrode active material can be controlled to a constant value depending on the position. Specifically, referring to FIG. 1, the negative electrode 13 according to the present invention includes a first negative electrode active layer 13c and a second negative electrode active layer 13b on both sides of the negative electrode current collector 13a. Here, the first negative electrode active layer 13c is positioned so as to be spaced apart from the winding center of the electrode assembly relative to the negative electrode current collector 13a, more so than the second negative electrode active layer 13b. As a result, the area ratio of the second negative electrode active layer 13b in contact with the positive electrode active layer (e.g., the first positive electrode active layer 11ac) is smaller than the area ratio of the first negative electrode active layer 13c in contact with the positive electrode active layer (e.g., the second positive electrode active layer 11bb). Generally, a first negative electrode active layer that is farther away from the winding center of a wound-type electrode assembly may have a relatively low charging performance because the lithium ion migration speed is higher than that of a second negative electrode active layer adjacent to the winding center. However, the present invention can lower the electrode resistance in the first negative electrode active layer 13c than the electrode resistance generated in the second negative electrode active layer 13b by orienting the ab-axis crystal plane of the carbon-based negative electrode active material contained in the first negative electrode active layer 13c at a predetermined angle with respect to the negative electrode current collector. As a result, the present invention can further improve the charging performance of the first negative electrode active layer 13c.

[0056] Specifically, the first negative electrode active layer 13c may have an ab-axis crystal plane of the carbon-based negative electrode active material aligned nearly perpendicular to the surface of the negative electrode current collector 13a, with an inclination of 60 to 120°. Here, "the carbon-based negative electrode active material is aligned nearly perpendicular to the negative electrode current collector" may mean that the crystal plane of the carbon-based negative electrode active material constituting the spherical particles, specifically, the ab-axis crystal plane indicating the planar direction of graphite having a two-dimensional structure among the crystal planes of graphite, is aligned with an inclination nearly perpendicular to the surface of the negative electrode current collector 13a. In this case, the planar direction of the graphite (i.e., the ab-axis crystal plane direction) may have an average inclination of 60 to 120°, preferably 70 to 110°, or 80 to 100°, with respect to the negative electrode current collector 13a. In comparison, the second negative electrode active layer 13b may have an ab-axis crystal plane of the carbon-based negative electrode active material aligned to have an inclination of less than 60° and / or more than 120° with respect to the surface of the negative electrode current collector 13a.

[0057] Similarly to the carbon-based negative electrode active material contained in the first negative electrode active layer 13c, the carbon-based negative electrode active material contained in the second negative electrode active layer 13b may be oriented such that its ab-axis crystal plane has a predetermined angle with respect to the surface of the negative electrode current collector 13a. However, the angle that the ab-axis crystal plane of the carbon-based negative electrode active material contained in the second negative electrode active layer 13b has with the negative electrode current collector may be smaller than the angle that the ab-axis crystal plane of the carbon-based negative electrode active material contained in the second negative electrode active layer 13b has with respect to the negative electrode current collector.

[0058] In addition, the alignment of the carbon-based negative electrode active material may be performed by a method commonly used in the art without any particular limitation, however, preferably, the alignment of the carbon-based negative electrode active material may be achieved by applying a magnetic field to the surface of each coated negative electrode active layer after applying a negative electrode slurry containing the carbon-based negative electrode active material to both sides of a negative electrode current collector during the preparation of the negative electrode.

[0059] The degree of alignment of the carbon-based negative electrode active material may be adjusted by the strength of the applied magnetic field, the exposure time, etc. For example, when a magnetic field is applied to the surface of the negative electrode slurry containing the carbon-based negative electrode active material for 1 to 10 seconds, the ab-axis crystal plane of the carbon-based negative electrode active material of the negative electrode slurry to which the magnetic field is applied for 10 seconds may have a larger inclination with respect to the surface of the negative electrode current collector than the carbon-based negative electrode active material of the negative electrode slurry to which the magnetic field is applied for 1 second. In the present invention, the magnetic field application to the negative electrode slurry may be performed with an intensity of 0.5T to 2.0T and for 1 to 60 seconds. Specifically, the magnetic field application may be performed with an intensity of 0.8T to 1.5T or 0.8T to 1.2T for 1 to 30 seconds or 1 to 20 seconds. In addition, the magnet used when applying the magnetic field to the negative electrode slurry may have a length ratio of 105% to 200% based on the width direction of the negative electrode slurry. Specifically, the length ratio may be 110% to 180%, 110% to 160%, 110% to 140%, 110% to 130%, 130% to 150%, or 105% to 120% based on the width direction length of the negative electrode slurry.

[0060] In the present invention, when a magnetic field is applied, the strength and / or duration of the magnetic field may be varied depending on the position of the first negative electrode active layer 13c and the second negative electrode active layer 13b, thereby inducing different orientations of the carbon-based negative electrode active material depending on the position of the negative electrode active layer.

[0061] As one example, when a magnetic field with a strength of 0.5 to 2.0 T is applied to the surface of the negative electrode slurry containing the carbon-based negative electrode active material, a magnetic field of 2.0 T is applied to the surface of the negative electrode slurry corresponding to the first negative electrode active layer 13c, and a magnetic field of 0.5 T is applied to the surface of the negative electrode slurry corresponding to the second negative electrode active layer 13b, thereby making it possible to realize different degrees of orientation of the first negative electrode active layer 13c and the second negative electrode active layer 13b.

[0062] The degree of alignment of the carbon-based negative electrode active material (eg, graphite) can be determined by molecular orientation and / or crystal structure analysis of the carbon-based negative electrode active material.

[0063] As an example, the degree of alignment of the carbon-based negative active material contained in the negative active layer can be determined by near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. In this case, the first negative active layer 13c has a carbon-based negative active material aligned nearly perpendicular to the negative current collector, and has an alignment degree (S 60 / 0 ) is the degree of alignment (S 60 / 0 ) can be smaller.

[0064] [Formula 1] S 60 / 0 =I60 B / A / I0 B / A

[0065] In the above formula 1, S 60 / 0 is the peak intensity ratio (I0 B / A ) when the X-ray incidence angle is 60° (I60 B / A ) value.

[0066] Unlike X-ray photoelectron spectroscopy (XPS), which measures the bond energy between atoms constituting a compound, near-edge X-ray absorption fine structure (NEXAFS) spectroscopy can only reflect the local structure near the carbon atom including the excited core electron and the surface structure of the particles of the measured carbon-based negative electrode active material. Therefore, the present invention can measure the degree of alignment of the carbon-based negative electrode active material contained in the negative electrode active layer by using a spectrum obtained by NEXAFS spectroscopy on the negative electrode active layer.

[0067] Specifically, when X-rays are irradiated onto the carbon atom (C) of a carbon-based negative electrode active material, the occupied electrons (K-shell inner shell electrons) present in the inner shell level (1s orbital) of the carbon atom absorb the X-ray energy and are excited to various unoccupied molecular orbitals, and the NEXAFS spectroscopy analysis uses the absorption spectrum observed at this time. Here, the unoccupied molecular orbitals include, when the carbon-based negative electrode active material is graphite, i) sp 2 π due to antibonding orbitals of bonds * orbitals, ii) sp orbitals that reflect crystallinity disorders (edge ​​planes, non-orientation, etc.) 3 σ due to antibonding orbitals of bonds * orbitals, and iii) Rydberg orbitals resulting from antibonding orbitals such as C-H and C-O bonds.

[0068] Carbon-based negative electrode active materials, such as graphite, have carbon atoms with sp 2 It has a crystal structure in which hexagonal net structures (see FIG. 4(a)) formed by bonding are stacked. Here, the two-dimensional plane (ab-axis crystal plane) of the hexagonal net surface is the basal plane, and the surface showing the edge of the hexagonal net (c-axis crystal plane) is the edge plane. In the edge plane of the carbon-based negative electrode active material, -COOH, -C=O, etc. may exist on the terminal carbon, so sp 3 Therefore, in order to analyze the crystal plane orientation and / or alignment of the carbon-based negative electrode active material, the sp 2 This can be determined by analyzing the orbital conditions.

[0069] The NEXAFS spectroscopy may be performed by irradiating the negative electrode active layer with X-rays having a fixed angle of incidence with respect to the negative electrode active layer. The spectroscopy may be performed by a total electron yield method that measures a current flowing through the negative electrode active layer to supplement photoelectrons emitted from the surface of the negative electrode active layer while scanning the energy of the irradiated X-rays from 280 eV to 320 eV.

[0070] At this time, since the synchrotron radiation is an X-ray that is linearly polarized by applying a magnetic field E, the intensity of the absorption peak observed may vary depending on the direction of incidence of the X-ray. Specifically, referring to FIG. 4(a), in the case of graphite, which is a carbon-based negative electrode active material, the sp 2 It has a hexagonal network structure via bonds (-C=C-), but the above sp 2 The bond is sp 2 σ orbitals parallel to the bond and sp 2 and a π orbital located in a direction perpendicular to the bond. Here, the σ orbital and the π orbital are antibonding orbitals, σ * Orbitals and π * Since it has a symmetric structure with nodes at the orbitals and the nucleus of the carbon atom, σ * Orbitals and π * The orbitals have the same orientation as the σ and π orbitals.

[0071] Therefore, as shown in Figure 4(b), the incident direction of the X-rays is sp 2 When the bond is parallel to the 1s level of carbon, * The intensity of the absorption peak excited to the sp level becomes larger, and conversely, 2 When the X-ray is incident perpendicular to the bond, the intensity of the absorption peak is small. 2 When the bond is parallel to the 1s level of carbon, the σ * The intensity of the absorption peak excited to the sp level becomes smaller, and conversely, 2 When the graphite is perpendicular to the bond, the intensity of the absorption peak is large. Due to this characteristic, when the graphite contained in the negative electrode active layer has a high degree of orientation as shown in Figure 3 (b), the antibonding vacant molecular orbitals of the graphite located on the surface of the negative electrode active layer are uniformly aligned, so when the incidence angle of the X-ray to the negative electrode active layer is changed, the spectrum shape changes significantly due to reinforcement and interference of the emitted photoelectrons. On the other hand, when the graphite contained in the negative electrode active layer has a low degree of orientation as shown in Figure 3 (a), the antibonding vacant molecular orbitals of the graphite located on the surface of the negative electrode active layer are non-uniformly aligned, so the spectrum shape hardly changes even when the incidence angle of the X-ray to the negative electrode active layer is changed.

[0072] In the present invention, in order to measure the degree of orientation of the carbon-based negative active material contained in the negative active layer, a NEXAFS spectroscopy is performed on the surface of the negative active layer. In this case, the NEXAFS spectroscopy is performed by irradiating X-rays at different angles of incidence (0° and 60°) on the negative active layer, and the 1s level to π level of carbon are measured for each angle of incidence. * The intensity of the absorption peak (peak A = 287 ± 0.2 eV) due to the transition to the 1s level of carbon versus σ * The ratio of the intensity of the absorption peak (peak B = 293 ± 0.2 eV) due to the transition to the level (I B / A ), the ratio of the intensity ratio between the incidence angles (60° and 0°) (S 60 / 0 =I60 B / A / I0 B / A ) can be used to quantitatively measure the orientation and / or alignment of the carbon-based negative electrode active material contained in the negative electrode active layer.

[0073] That is, the degree of orientation of the carbon-based negative electrode active material contained in the negative electrode active layer is, as represented by i) Equation 2, first, determined by the π * Absorption peak intensity (peak A = 287 ± 0.2 eV) due to transition to the level (I60 A ) from the carbon 1s level to σ * Absorption peak intensity (peak B = 293 ± 0.2 eV) due to transition to the level (I60 B ) percentage (I60 B / A ) can be calculated. Next, ii) π * The intensity of the absorption peak (peak A = 287 ± 0.2 eV) due to the transition to the level (I0 A ) from the C1s carbon level to σ * The intensity of the absorption peak (peak B = 293 ± 0.2 eV) due to the transition to the level (I0 B ) percentage (I0 B / A Finally, iii) the ratio (S 60 / 0 =I60 B / A / I0 B / A ) can be evaluated.

[0074] [Formula 2] I60 B / A =I60 B / I60 A

[0075] [Formula 3] I0 B / A =I0 B / I0 A

[0076] In Equation 2 and Equation 3, I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.

[0077] Here, the above formula 1(S 60 / 0 ) is closer to 1, the lower the orientation of the ab-axis crystal plane of the graphite, which is a carbon-based negative electrode active material, with respect to the negative electrode current collector, and the higher the degree of alignment (OI). 60 / 0 ) is closer to 0, the more the ab-axis crystal plane of the graphite, which is a carbon-based negative electrode active material, is oriented relative to the negative electrode current collector, and the smaller the degree of alignment (OI).

[0078] The first negative electrode active layer 13c according to the present invention has a value according to Equation 1 (S 60 / 0) may be 1.0 or less, more specifically, 0.9 or less, 0.8 or less, 0.7 or less, 0.5 or less, 0.05 to 0.7, 0.05 to 0.5, 0.05 to 0.4, 0.1 to 0.7, 0.3 to 0.7, or 0.5 to 0.8. In addition, the second negative electrode active layer 13b may satisfy the value (S 60 / 0 ) may exceed 0.5, and more specifically may satisfy 0.5 to 1.5, 0.5 to 1.2, 0.7 to 1.0, 0.8 to 1.0, or 0.7 to 1.1. In addition, the second negative electrode active layer 13b may satisfy the average of S of the first negative electrode active layer 13c. 60 / 0 Specifically, the second negative electrode active layer 13b may have a ratio of S of the first negative electrode active layer 13c to S of the first negative electrode active layer 13c. 60 / 0 The ratio may be 101% to 130%, or 105% to 115%.

[0079] In the present invention, the degree of alignment (S 60 / 0 ) as described above, the electrode resistance generated in the first negative electrode active layer 13c of the negative electrode provided with the wound-type electrode assembly can be made lower than the electrode resistance generated in the second negative electrode active layer 13b. In addition, such a reduction in the electrical resistance of the first negative electrode active layer 13c can further improve the charge / discharge performance of the electrode assembly and reduce the difference in the rate at which the negative electrode active layers disposed on both sides of the negative electrode current collector deteriorate, thereby further improving the life of the secondary battery.

[0080] As another example, the degree of alignment of the carbon-based negative active material contained in the negative active layer may be determined by X-ray diffraction (XRD) spectroscopy. In this case, the first negative active layer 13c has an ab-axis crystal plane of the carbon-based negative active material aligned nearly perpendicular to the negative current collector, and the degree of alignment (OI) of the carbon-based negative active material is expressed by the following Equation 4: sliding ) is the degree of alignment (OI) of the carbon-based negative electrode active material contained in the flat part. flat ) can be smaller.

[0081] [Formula 4] OI=I 004 / I 110

[0082] In Equation 4, I 004 represents the area of ​​the peak showing the (004) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer, I 110 represents the area of ​​the peak indicating the (110) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer.

[0083] The crystal plane orientation of the carbon-based negative electrode active material can be determined by a crystal plane analysis of the carbon-based negative electrode active material, such as X-ray diffraction spectroscopy. The degree of alignment (OI) of the carbon-based negative electrode active material represented by the above formula 4 can be an index indicating the direction in which the crystal structure of the carbon-based negative electrode active material is aligned during X-ray diffraction measurement, specifically, the degree to which the ab-axis crystal plane indicating the two-dimensional planar structure of the carbon-based negative electrode active material is aligned with respect to the surface of the negative electrode current collector. For example, when the negative electrode active layer contains graphite as the carbon-based negative electrode active material, the negative electrode active layer exhibits 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2°, which are peaks for graphite during X-ray diffraction measurement of the negative electrode active layer. This refers to the (002) plane, (100) plane, (101)R plane, (101)H plane, (004) plane, and (110) plane of the graphite crystal plane contained in the negative electrode active layer. In general, in the case of graphite, graphene layers are placed on the a-axis and b-axis planes, and such graphene layers are stacked along the c-axis to have a hexagonal or rhombohedral crystal structure. Here, the crystal plane peak is a peak that indicates the plane characteristics of such a crystal structure. In addition, the peak that appears at 2θ=43.4±0.2° may be considered to be an overlap of the (101)R plane of the carbon-based material and the peak corresponding to the (111) plane of the current collector, for example, Cu.

[0084] In the present invention, the degree of alignment (OI) of graphite can be measured by the area ratio of the peak at 2θ=54.7±0.2° representing the (004) plane and the peak at 2θ=77.5±0.2° representing the (1,1,0) plane, specifically, the area ratio obtained by integrating the intensities of the above peaks. In addition, the X-ray diffraction was measured using CuK α rays as a target line, and the target line was extracted and measured using a monochromator device to improve the peak intensity resolution. At this time, the measurement conditions were 2θ=10° to 90°, a scan speed (° / s) of 0.044 to 0.089, and a step size of 0.026° / step.

[0085] In addition, the (004) plane appearing at 2θ=54.7±0.2° indicates the thickness direction characteristic (c-axis direction characteristic) of the layered structure in which the two-dimensional planar structure of the graphite layers is laminated, and the (110) plane appearing at 2θ=77.5±0.2° indicates the planar characteristic (ab-axis direction characteristic) of the laminated graphite layers. Therefore, the smaller the (004) plane peak indicating the thickness direction characteristic of the graphite layer plane, and the larger the (110) plane peak indicating the planar characteristic of the graphite layer, the higher the angle at which the graphite plane is aligned with respect to the negative electrode current collector surface. In other words, the closer the degree of alignment (OI) value is to 0, the closer the angle or inclination of the graphite layer plane to the negative electrode current collector surface is to 90°, and the larger the value is, the closer the inclination to the negative electrode current collector surface is to 0° or 180°.

[0086] In this regard, the first negative electrode active layer 13c according to the present invention may have a relatively low degree of alignment (OI) compared to the carbon-based negative electrode active material contained in the second negative electrode active layer 13b since the ab-axis crystal plane of the carbon-based negative electrode active material is aligned nearly perpendicular to the negative electrode current collector.

[0087] Specifically, the degree of alignment (OI) of the carbon-based negative electrode active material contained in the first negative electrode active layer 13c 1st) may be 0.1 to 2.0, and more specifically may be 0.1 to 1.5, 0.1 to 1.0, 0.2 to 1.5, 0.5 to 1.5, 0.8 to 1.5, 1.0 to 2.0, 0.3 to 1.2, 0.6 to 1.2, 0.15 to 0.8, 0.15 to 0.6, 0.15 to 0.5, 0.2 to 0.5, 0.2 to 0.4, 0.25 to 0.45, 0.3 to 0.5, 0.3 to 0.8, 0.4 to 0.7, or 0.35 to 0.6.

[0088] The present invention is directed to the degree of alignment (OI) of the carbon-based negative electrode active material contained in the first negative electrode active layer 13c. 1st ) within the above range, the electrode resistance can be reduced while improving the lithium ion mobility at the negative electrode end during charging and discharging of the battery. Such a reduction in electrode resistance can further improve the charge and discharge performance of the electrode assembly and can reduce the difference in the rate of deterioration of the negative electrode active layers disposed on both sides of the current collector, thereby further improving the life of the secondary battery.

[0089] In addition, the carbon-based negative electrode active material contained in the second negative electrode active layer 13b is oriented together with the carbon-based negative electrode active material contained in the first negative electrode active layer 13c, and the ab-axis crystal plane may have a certain angle or inclination with respect to the surface of the negative electrode current collector. As a result, the carbon-based negative electrode active material contained in the second negative electrode active layer 13b has an alignment degree (OI 2nd Specifically, the degree of alignment (OI) of the second negative electrode active layer may be within a predetermined range. 2nd ) is the degree of alignment (OI) of the first negative electrode active layer 1st ) as a standard, and more specifically, the ratio may be 101% to 140%, 101% to 130%, 101% to 120%, 101% to 110%, 105% to 120%, 105% to 130%, 105% to 140%, 110% to 130%, 110% to 120%, 115% to 130%, or 120% to 140%.

[0090] In the present invention, the degree of alignment (OI) of the carbon-based negative electrode active material contained in each of the first negative electrode active layer 13c and the second negative electrode active layer 13b is measured. 1st and O.I. 2ndBy adjusting the degree of alignment (OI) of the carbon-based negative electrode active material contained in each of the first and second negative electrode active layers 13c to satisfy the above range, the lithium mobility of the entire negative electrode active layers 13b and 13c can be increased while the electrical resistance of the first negative electrode active layer 13c can be more effectively reduced, thereby improving the energy density of the negative electrode. 1st and O.I. 2nd When the ratio of the carbon-based negative electrode active material is increased significantly within the above range, the degree of alignment (OI 1st and O.I. 2nd ) becomes large, which accelerates the deterioration of the negative electrode active layer at different positions, thereby shortening the life of the negative electrode.

[0091] As another example, when the degree of alignment of the carbon-based negative electrode active material contained in the negative electrode active layer is determined by X-ray diffraction (XRD) spectroscopic analysis, the first negative electrode active layer 13c may satisfy a degree of divergence (DD) value defined by the following Equation 5 within a certain range, and the value may be greater than the DD value of the second negative electrode active layer 13b.

[0092] [Formula 5] DD(Degree of Divergence)=(I a / I total ) x 100

[0093] In the above formula 5, I a represents the sum of the peak intensities appearing at non-planar angles during XRD measurement using CuKα radiation, I total represents the sum of peak intensities appearing at all angles during XRD measurement using CuKα radiation.

[0094] Here, the above-mentioned non-planar angles are 2θ=42.4±0.2°, 43.4±0.2°, 44.6±0.2°, and 77.5±0.2° when measured by XRD (X-ray diffraction) using CuKα radiation, and these angles indicate the (100) plane, the (101)R plane, the (101)H plane, and the (110) plane.

[0095] The DD value according to the above formula 5 represents the ratio of graphite crystal planes having a two-dimensional structure among all the faces of the carbon-based negative active material in the XRD spectroscopic analysis, and the two-dimensional structure means a layered structure of graphite that is directly related to electrical properties. That is, the above formula 5 represents the degree to which the two-dimensional structure of graphite that improves electrical properties is aligned with respect to the negative current collector 13a, and the larger the value, the more the graphite is aligned perpendicular to the negative current collector 13a.

[0096] The first negative electrode active layer of the present invention has a DD value according to Formula 5 that is greater than the DD value of the second negative electrode active layer, so that the electrode assembly may have uniform charging performance.

[0097] As one example, the first negative electrode active layer may have a DD value of 20 to 60, and the second negative electrode active layer may have a small DD value that is a ratio of 1% to 95% based on the DD value of the first negative electrode active layer. More specifically, the first negative electrode active layer may have a DD value of 25 to 40 or 40 to 55, and in this case, the second negative electrode active layer may have a DD value of 5 to 20 or 20 to 45 (a ratio of 60 to 85% based on the DD value of the first negative electrode active layer).

[0098] Furthermore, the wound electrode assembly includes a rectangular positive electrode and a negative electrode wound with a separator. Therefore, the first negative electrode active layer 13c included in the negative electrode may have different positions within the wound electrode assembly, and the alignment degree of the carbon-based negative electrode active material included therein may vary depending on the position of the first negative electrode active layer 13c. Specifically, as shown in FIG. 2, the wound electrode assembly includes a rectangular negative electrode 13 having a first negative electrode active layer 13c and a second negative electrode active layer 13b provided on both sides of a negative electrode current collector 13a, in a rolled up form based on the winding center.

[0099] In such a wound electrode assembly, when the secondary battery is charged and discharged for a long time, lithium ions are continuously inserted and removed from the negative active material, causing repeated contraction and expansion of the negative active material. At this time, the insertion and removal of lithium ions reduces the alignment of the ab-axis crystal plane of the carbon-based negative active material contained in the negative active layer. In addition, the contraction and expansion of the negative active material applies stress to the negative current collector, inducing wrinkles, loosening, buckling, etc. of the negative current collector, and further promoting the deterioration of the alignment of the ab-axis crystal plane of the carbon-based negative active material. In particular, as shown in FIG. 2, the part of the negative current collector located on the outer side B rather than the inner side A based on the winding center of the wound electrode assembly is more likely to be induced to wrinkle, loosen, buckle, etc. Therefore, even if the negative active layer is a single layer, the degree of damage to the alignment of the ab-axis crystal plane of the carbon-based negative active material may be large depending on the position in the electrode assembly after winding.

[0100] However, in the present invention, the degree of alignment (S 60 / 0 , O.I. 1st and / or DD), it is possible to minimize the alignment damage and / or loss of the carbon-based negative electrode active material even after long-term charging and discharging of the secondary battery.

[0101] Specifically, the present invention controls the orientation of the carbon-based negative active material contained in the first negative active layer from the inside to the outside with respect to the winding center of the electrode assembly, and the degree of alignment at the outermost shell of the wound negative electrode has the above-mentioned ratio to the degree of alignment at the winding center. In this case, as shown in FIG. 2, the crystal plane of the carbon-based negative active material contained in the outermost shell of the wound negative electrode has a relatively low inclination with the negative electrode current collector compared to the carbon-based negative active material contained in the winding center. In this case, the directions of the stress generated in each region during volume expansion due to the insertion of lithium ions are different and opposite to each other. As a result, the total stress applied to the negative electrode current collector and the amount of stress generated in the outermost shell can be reduced. As a result, there is an advantage in that the orientation damage and / or loss of the carbon-based negative active material generated during long-term charging and discharging of the secondary battery can be minimized.

[0102] For this purpose, the present invention provides a method for adjusting the degree of alignment (S) of the first negative electrode active layer so that the inclination of the ab-axis crystal plane of the carbon-based negative electrode active material contained in the first negative electrode active layer with respect to the negative electrode current collector decreases at the above-mentioned rate from the inside to the outside based on the winding center of the electrode assembly. 60 / 0 , O.I. 1st and / or DD).

[0103] As an example, the first negative electrode active layer 13c has an alignment degree (S ex60 / 0 ) is the alignment degree (S in60 / 0 ) as a standard, the ratio may be 101% to 150%, specifically, the ratio may be 101% to 140%, 101% to 130%, 101% to 120%, 101% to 110%, 105% to 120%, 105% to 130%, 105% to 140%, 110% to 130%, 110% to 120%, 115% to 130%, or 120% to 140%.

[0104] As another example, the first negative electrode active layer 13c has an alignment degree (OI) at the outermost surface of the electrode assembly. ex1st ) is the alignment degree (OI in1st ) as a standard, the ratio may be 101% to 150%, specifically, the ratio may be 101% to 140%, 101% to 130%, 101% to 120%, 101% to 110%, 105% to 120%, 105% to 130%, 105% to 140%, 110% to 130%, 110% to 120%, 115% to 130%, or 120% to 140%.

[0105] As another example, the first negative electrode active layer 13c is a DD layer at the outermost layer of the electrode assembly. ex1st The value is the DD at the winding center of the electrode assembly. in1st The percentage may be 50% to 99% based on the value, and specifically may be 95% to 75%, or 80% to 95%.

[0106] The degree of alignment of the carbon-based negative active material contained in the winding center and the outermost shell of the first negative active layer 13c may be realized by a method commonly applicable in the art. In the present invention, the degree of alignment may be realized by (1) controlling the orientation conditions when the crystal plane of the carbon-based negative active material contained in the first negative active layer 13c is oriented, or (2) controlling the winding conditions when the manufactured negative electrode is wound together with the positive electrode and the separator. Here, the winding conditions may refer to the winding speed, winding thickness, etc. of the electrode. The winding speed when the electrode assembly is wound and the thickness of the wound electrode assembly may affect the stress applied to the negative current collector included in the negative electrode. The stressed negative current collector may reduce the alignment of the carbon-based negative active material of the negative active layer aligned on the surface. Therefore, by controlling the stress applied to the negative electrode current collector when the electrode assembly is wound, the degree of alignment of the carbon-based negative electrode active material at the winding center and the outermost shell of the first negative electrode active layer 13c can be realized.

[0107] As one example, the present invention may apply magnetic fields of different strengths to the negative electrode slurries corresponding to the first and second negative electrode active layers after applying negative electrode slurry including a carbon-based negative electrode active material to both sides of a negative electrode current collector. In this case, the magnetic field applied to the negative electrode slurry corresponding to the first negative electrode active layer may not have a constant strength but may increase or decrease in strength at a predetermined rate, thereby implementing a difference in the degree of alignment between regions of the carbon-based negative electrode active material in the negative electrode slurry (e.g., the winding center region and the outermost shell region of the negative electrode active layer).

[0108] As another example, the present invention may manufacture a negative electrode by applying a negative electrode slurry containing a carbon-based negative electrode active material to both sides of a negative electrode current collector, applying magnetic fields of different strengths to the negative electrode slurries corresponding to the first and second negative electrode active layers, and drying and rolling them. The manufactured negative electrode may then be wound with a positive electrode and a separator to manufacture a wound-type electrode assembly, and the first negative electrode active layer 13c and the second negative electrode active layer 13b may be embodied with different degrees of orientation by controlling the winding speed to gradually increase after the start of winding.

[0109] In addition, the wound electrode assembly according to the present invention may be adjusted so that the loading amount of the negative electrode satisfies a predetermined range. For example, the negative electrode provided in the wound electrode assembly may be adjusted so that the loading amount of the negative electrode satisfies a predetermined range. 2 ~500mg / 25cm 2 More specifically, the first negative electrode active layer and the second negative electrode active layer included in the negative electrode may each have a loading amount of 250 mg / 25 cm. 2 ~450mg / 25cm 2 , 250mg / 25cm 2 ~400mg / 25cm 2 , 250mg / 25cm 2 ~350mg / 25cm 2 , 250mg / 25cm 2 ~300mg / 25cm 2 , 270mg / 25cm 2 ~380mg / 25cm 2 , 300mg / 25cm 2 ~500mg / 25cm 2 , 380mg / 25cm 2 ~450mg / 25cm 2 , or 400 mg / 25 cm 2 ~500mg / 25cm 2 The loading amount may be 0.01 to 0.01.

[0110] The diameter of the wound electrode assembly of the present invention may be 30 mm or more. Specifically, the lower limit of the diameter of the electrode assembly may be 35 mm or more, 37.5 mm or more, 40 mm or more, 42.5 mm or more, or 45 mm or more, and the upper limit may be 100 mm or less, 90 mm or less, 80 mm or less, 70 mm or less, 60 mm or less, or 50 mm or less.

[0111] As one example, the wound electrode assembly according to the present invention may have a diameter of 35 mm to 75 mm, and more specifically, may have a diameter of 35 mm to 70 mm, 35 mm to 65 mm, 35 mm to 60 mm, 38 mm to 55 mm, 40 mm to 50 mm, or 42 mm to 48 mm.

[0112] The present invention has the advantage that the energy density and output of the electrode assembly can be significantly increased by controlling the diameter of the wound-type electrode assembly and the loading amount of the negative electrode provided in the wound-type electrode assembly within the above-mentioned range, and at the same time, the volume change of the negative electrode during charging and discharging of the secondary battery can be effectively suppressed, making it easy to improve problems caused by the volume change.

[0113] Furthermore, the first negative electrode active layer has an intensity ratio (I 004 / I 002 Specifically, the first negative electrode active layer can be controlled to have the above ratio (I 004 / I 002 The present invention can control the intensity ratio (I 004 / I 002 ) within the above range, an increase in DC internal resistance can be suppressed, so that the charge / discharge performance at the winding center of the electrode assembly and the charge / discharge performance at the outer shell can be uniformly realized, and uneven deterioration of the electrode assembly can be prevented.

[0114] Meanwhile, the negative electrode active layer according to the present invention may further selectively contain a conductive material, a binder, other additives, and the like, in addition to the negative electrode active material, as necessary.

[0115] The conductive material may include, but is not limited to, one or more of carbon black, acetylene black, ketjen black, carbon nanotubes, carbon fibers, and the like.

[0116] For example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc., alone or in combination, as a conductive material.

[0117] At this time, the content of the conductive material may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 0.5 to 2 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the conductive material within the above range, the present invention can prevent a decrease in charge capacity due to an increase in the resistance of the negative electrode caused by a low content of the conductive material. In addition, it can prevent problems such as a decrease in the content of the negative electrode active material due to an excessive amount of the conductive material, resulting in a decrease in charge capacity, or a decrease in rapid charge characteristics due to an increase in the loading amount of the negative electrode active layer.

[0118] In addition, the binder is a component that aids in bonding between the active material and the conductive material and bonding to the current collector, and may be suitably applied within a range that does not deteriorate the electrical properties of the electrode. Specifically, the binder may include any one or more selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, and fluororubber.

[0119] The content of the binder may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the binder contained in the negative electrode active layer within the above range, the present invention can prevent a decrease in adhesive strength of the active layer due to a low content of the binder, or a decrease in electrical properties of the electrode due to an excessive amount of the binder.

[0120] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, nickel, titanium, calcined carbon, etc., and in the case of copper or stainless steel, it may be surface-treated with carbon, nickel, titanium, silver, etc. The average thickness of the negative electrode current collector may be suitably 1 to 500 μm, taking into consideration the conductivity and total thickness of the negative electrode to be manufactured.

[0121] In addition, when the creep rate of the negative electrode current collector is measured under conditions of 22±2°C and a tensile force of 300 MPa, the rate of change in length of the negative electrode current collector after 2 seconds from application of the tensile force (C2) and after 60 seconds from application of the tensile force (C60) according to time can satisfy a rate of 20 to 50 μm / sec.

[0122] Here, the term "creep rate" refers to the degree of deformation of the negative electrode current collector over time, and indicates the rate of change in length of the negative electrode current collector over time when a constant force is applied to a metal sheet at a specific temperature. In the present invention, the creep rate of the entire negative electrode current collector is controlled to satisfy the above range, thereby reducing the stress on the negative electrode current collector generated on the outer shell of the wound-type electrode assembly during charging and discharging of the battery, thereby improving wrinkles, unraveling, buckling, etc. of the negative electrode.

[0123] The wound electrode assembly according to the present invention further includes a positive electrode including a positive electrode active layer including a positive electrode active material on a positive electrode current collector, wherein the positive electrode active layer may further include a conductive material, a binder, and other additives, as necessary, in addition to the positive electrode active material.

[0124] The positive electrode active material is a material capable of electrochemically reacting on a positive electrode current collector, and may include at least one of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2 capable of reversibly intercalating and deintercalating lithium ions.

[0125] [Chemical formula 1] Li x[Ni y Co z Mn w M 1 v ]O2

[0126] [Chemical formula 2] LiM 2 p Mn q P r O4

[0127] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are 1.0≦x≦1.30, 0.5≦y<1, 0 <z≦0.3、0<w≦0.3、0≦v≦0.1であり、かつy+z+w+v=1であり、 M 2 is Ni, Co or Fe, p is 0.05≦p≦1.0, q is 1-p or 2-p; r is 0 or 1.

[0128] The lithium metal oxides represented by Chemical Formula 1 and Chemical Formula 2 above are materials containing high amounts of nickel (Ni) and manganese (Mn), respectively, and when used as a positive electrode active material, have the advantage of being capable of stably supplying high capacity and / or high voltage electricity.

[0129] In this case, the lithium metal oxide represented by the above chemical formula 1 is LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O 2、 LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, etc., which may be used alone or in combination. The lithium metal oxide represented by the above formula 2 may be LiNi 0.7 Mn 1.3 O4, LiNi 0.5 Mn 1.5 O 4、 LiNi 0.3 Mn 1.7 O 4、 LiFePO4, LiFe 0.8 Mn 0.2 PO4, LiFe 0.5 Mn 0.5 PO4, etc., which may be used alone or in combination.

[0130] The positive electrode active material may be included in an amount of 85 parts by weight or more, specifically 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more, based on the weight of the positive electrode active layer.

[0131] The positive electrode active layer may further include a conductive material, a binder, and other additives in addition to the positive electrode active material.

[0132] In this case, the conductive material is used to improve the electrical performance of the positive electrode, and may be any conductive material commonly used in the art. Specifically, the conductive material may include at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, denka black, ketjen black, super P, channel black, furnace black, lamp black, thermal black, graphene, and carbon nanotubes.

[0133] The conductive material may be contained in an amount of 0.1 to 5 parts by weight, based on the weight of each positive electrode active layer, specifically 0.1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, 1 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 part by weight.

[0134] In addition, the binder plays a role of binding the positive electrode active material, the positive electrode additive, and the conductive material to each other, and may be used without any particular limitation as long as it has such a function. Specifically, the binder may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As an example, the binder may include polyvinylidene fluoride.

[0135] The binder may be included in an amount of 1 to 10 parts by weight, specifically 2 to 8 parts by weight, or 1 to 5 parts by weight, based on the weight of each positive electrode active layer.

[0136] The total thickness of the positive electrode active layer is not particularly limited, but may be specifically 50 μm to 300 μm, more specifically 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm, or 150 μm to 190 μm.

[0137] In addition, the positive electrode may use a positive electrode current collector having high conductivity without inducing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. may be used, and in the case of aluminum or stainless steel, those surface-treated with carbon, nickel, titanium, silver, etc. may also be used. In addition, the average thickness of the current collector may be suitably applied to be 3 to 500 μm, taking into consideration the conductivity and total thickness of the positive electrode to be manufactured.

[0138] Furthermore, the separator interposed between the positive and negative electrodes of each unit cell is an insulating thin film having high ion permeability and mechanical strength, and is not particularly limited as long as it is a commonly used one in the art. Specifically, the separator may include at least one polymer selected from polypropylene, polyethylene, and polyethylene-propylene copolymers, which are chemically resistant and hydrophobic. The separator may have a porous polymer substrate such as a sheet or nonwoven fabric containing the above-mentioned polymer. In some cases, the separator may have a composite separator formed by coating organic or inorganic particles on the porous polymer substrate with an organic binder. The separator may have an average pore diameter of 0.01 to 10 μm and an average thickness of 5 to 300 μm.

[0139] The wound electrode assembly according to the present invention has the above-mentioned configuration, and therefore can realize uniform charging performance of the electrode assembly, and can improve performance degradation caused by wrinkles, loosening, buckling, etc. of the negative electrode current collector during long-term charging and discharging. Therefore, a secondary battery including the same has the advantage of excellent life characteristics and long-term charging and discharging performance.

[0140] <Lithium secondary battery> Further, in one embodiment, the present invention provides There is provided a lithium secondary battery including the above-described wound-type electrode assembly of the present invention.

[0141] The lithium secondary battery according to the present invention includes an electrode assembly in which a rectangular positive electrode, a separator, and a negative electrode are sequentially arranged and wound. In this case, the electrode assembly includes the wound-type electrode assembly according to the present invention described above, which can realize uniform charging performance of the electrode assembly and can improve performance degradation caused by wrinkles, loosening, buckling, etc. of the negative electrode current collector during long-term charging and discharging. Therefore, a secondary battery including the electrode assembly has excellent life characteristics and long-term charging and discharging performance.

[0142] The winding type electrode assembly has the same structure as the winding type electrode assembly of the present invention described above, and therefore a detailed description thereof will be omitted.

[0143] The lithium secondary battery includes the electrode assembly and an electrolyte composition in which a lithium salt is dissolved in a non-aqueous organic solvent.

[0144] Examples of the electrolyte composition include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0145] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0146] The organic solvent may be used without any particular limitation as long as it can serve as a medium through which ions involved in the electrochemical reaction of the battery can move. For example, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a C2-C20 straight-chain, branched or cyclic hydrocarbon group, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to 9 to provide excellent electrolyte performance.

[0147] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2.

[0148] The lithium salt may be used at a concentration within the range of 0.1 M to 2.0 M. When the lithium salt concentration is within the above range, the electrolyte has suitable conductivity and viscosity, and therefore can exhibit excellent electrolyte performance and allow lithium ions to migrate effectively.

[0149] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.

[0150] Meanwhile, the lithium secondary battery according to the present invention may be, but is not limited to, a cylindrical secondary battery or a prismatic secondary battery to which a wound-type electrode assembly may be applied. As one example, the lithium secondary battery according to the present invention may be a prismatic secondary battery.

[0151] In addition, the lithium secondary battery stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, and in electric vehicles such as hybrid electric vehicles (HEVs).

[0152] The present invention will now be described in more detail with reference to examples and experimental examples.

[0153] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.

[0154] <Production Examples 1 to 8. Production of negative electrodes for winding electrode assemblies> Natural graphite (sphericity: 0.9±0.2) was prepared as the negative electrode active material, carbon black was prepared as the conductive material, and carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) were prepared as the binder. 95 parts by weight of natural graphite, 1 part by weight of carbon black, 1.5 parts by weight of carboxymethyl cellulose (CMC), and 2.5 parts by weight of styrene butadiene rubber (SBR) were mixed with water to a solid content of 50% to form a negative electrode slurry, which was then simultaneously cast onto both sides of a copper sheet (thickness: 10 μm) being transported roll-to-roll.

[0155] Then, magnets were placed on the top and bottom of the copper thin plate. At this time, the magnets were adjusted to have a length ratio of 110 to 120% based on the width direction length of the negative electrode slurry. Then, a magnetic field was applied to each negative electrode slurry (moving speed: 1 to 3 m / min) while moving using the magnets to induce vertical orientation of the natural graphite in the negative electrode slurry. At this time, the magnetic field was applied under the following conditions.

[0156] [Table 1]

[0157] The copper sheet coated with the negative electrode slurry was then dried in a vacuum oven at 130°C, and rolled to a density of 1.63±0.2 g / cc and slit to manufacture negative electrodes. In order to confirm the degree of alignment of the carbon-based negative electrode active material contained in the first and second negative electrode active layers of each of the manufactured negative electrodes, i) near-edge X-ray fluorescence spectroscopy (NEXAFS) and X-ray diffraction (XRD) were performed on the first and second negative electrode active layers, respectively, to measure the spectra. The spectroscopic analysis conditions were as follows:

[0158] (1) Near-edge X-ray absorption fine structure (NEXAFS) - Acceleration voltage: 1.0GeV~1.5GeV - Storage current: 80~350mA - Angle of incidence: 60° or 0°

[0159] (2) X-ray diffraction (XRD) - Target: Cu (Kα line) graphite monochromator - Slit: Divergence slit = 1 degree, Receiving slit = 0.1mm, Scattering slit = 1 degree

[0160] From the spectra obtained using the following Equations 1 to 5, the degree of alignment (S 60 / 0 , OI and / or DD) were calculated. In addition, ii) an X-ray diffraction (XRD) spectroscopic analysis was additionally performed on the region that would become the winding center and the region that would become the outermost shell in the first negative electrode active layer, and the degree of alignment (OI) of the carbon-based negative electrode active material contained in the region that would become the outermost shell and the region that would become the winding center was calculated. ex / OI in Finally, iii) the ratio of the intensity of the peak representing the (004) plane to the intensity of the peak representing the (002) plane from the spectrum obtained during the X-ray diffraction (XRD) spectroscopic analysis of the first negative electrode active layer (I 004 / I 002 The calculated results are shown in Tables 2 and 3 below.

[0161] [Formula 1] S 60 / 0 =I60B / A / I0 B / A

[0162] [Formula 2] I60 B / A =I60 B / I60 A

[0163] [Formula 3] I0 B / A =I0 B / I0 A

[0164] In formulas 1 to 3, S 60 / 0 is the peak intensity ratio (I0 B / A ) when the X-ray incidence angle is 60° (I60 B / A ) value, I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°.

[0165] [Formula 4] OI=I 004 / I 110

[0166] In the above formula 4, I 004 represents the area integral value of the peak representing the (004) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer, I 110 represents the area integral value of the peak indicating the (110) crystal plane in X-ray diffraction (XRD) spectroscopic analysis of the negative electrode active layer.

[0167] [Formula 5] DD(Degree of Divergence)=(I a / I total ) x 100

[0168] In the above formula 5, I a represents the sum of the peak intensities appearing at non-planar angles during XRD measurement using CuKα radiation, I total represents the sum of peak intensities appearing at all angles during XRD measurement using CuKα radiation.

[0169] [Table 2]

[0170] [Table 3]

[0171] <Examples 1 to 5 and Comparative Examples 1 to 3. Production of Wound-Type Electrode Assembly> The positive electrode active material is LiNi with a particle size of 5 μm. 0.7 Co 0.1 Mn 0.1 Al 0.1 O2 was prepared and mixed with polyvinylidene fluoride as a carbon-based conductive agent and binder in N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 to form a slurry, which was then cast onto an aluminum sheet, dried in a vacuum oven at 120°C, and rolled to produce a positive electrode.

[0172] A winding-type electrode assembly was manufactured by interposing a separator made of 18 μm polypropylene between the obtained positive electrode and the negative electrode manufactured in each of Manufacturing Examples 1 to 8 and winding them up. The type of negative electrode applied to each electrode assembly is shown in Table 4 below.

[0173] [Table 4]

[0174] <Experimental Example 1> In order to evaluate the performance of the wound-type electrode assembly according to the present invention after long-term charging and discharging, the following experiment was carried out.

[0175] Specifically, each of the wound electrode assemblies manufactured in the examples and comparative examples was inserted into a cylindrical battery can, and a non-aqueous electrolyte was injected to manufacture a secondary battery. Then, while maintaining the temperature at 45° C., each of the cylindrical secondary batteries manufactured was charged and discharged 200 times in CC / CV mode, and the initial charge capacity was compared with the capacity after the 200th charge to calculate the charge capacity retention rate, thereby confirming the degradation degree of the electrode assembly.

[0176] In addition, the secondary batteries that had been charged and discharged 200 times were disassembled, and the negative electrode morphology of the wound electrode assembly was evaluated with the naked eye. If there was no change in the negative electrode morphology, it was indicated with "x", and if wrinkles and / or buckling or melting occurred in the negative electrode, it was indicated with "o". The results are shown in Table 5 below.

[0177] [Table 5]

[0178] As shown in Table 5, the wound electrode assembly according to the present invention has a high capacity retention rate during long-term charge and discharge, and the morphological change of the negative electrode is suppressed. This indicates that the charging performance of the winding center and the outer shell of the wound electrode assembly during long-term charge and discharge of the battery is uniform, suppressing degradation, and reducing stress due to expansion stress of the negative electrode.

[0179] From these results, it can be seen that the wound electrode assembly according to the present invention can realize uniform charging performance of the electrode assembly by controlling the degree of orientation of the carbon-based negative electrode active material contained in the negative electrode active layer according to the degree of separation of the negative electrode active layer provided on both sides of the negative electrode current collector with respect to the winding center of the electrode assembly, and can also improve performance degradation due to wrinkles, unraveling, buckling, etc. of the negative electrode current collector during long-term charging and discharging.

[0180] Although the present invention has been described above with reference to preferred embodiments, it will be understood that a person skilled in the art or having ordinary knowledge in the art may make various modifications and changes to the present invention without departing from the spirit and technical scope of the present invention as described in the claims below.

[0181] Therefore, the technical scope of the present invention is not limited to the contents described in the Summary of the Invention of the specification, but is defined by the claims.

Claims

1. A wound electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the negative electrode includes a negative electrode current collector, and a first negative electrode active layer and a second negative electrode active layer formed on both sides of the negative electrode current collector, the first negative electrode active layer being located farther away from a winding center of the electrode assembly than the second negative electrode active layer; The first negative electrode active layer has an alignment degree (S ex60/0 ) is the degree of alignment (S in60/0 ) smaller than [Formula 1] S 60/0 =I60 B/A / I0 B/A [Formula 2] I60 B/A =I60 B / I60 A [Formula 3] I0 B/A =O0 B / A0 A In the formulas 1 to 3, S 60/0 is the peak intensity ratio (I0 B/A ) at an X-ray incidence angle of 60° (I60 B/A ) I60 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 60°, I60 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 60°, I0 A represents the intensity of the strongest peak among the peaks present at 286±1.0 eV when the X-ray incident angle is 0°, I0 B represents the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the X-ray incident angle is 0°, for a wind-up electrode assembly.

2. The first negative electrode active layer has an alignment degree (O.I) represented by the following Formula 4: 1st ) is the alignment degree (O.I.) of the second negative electrode active layer 2nd ) smaller than [Formula 4] O.I=I 004 / I 110 In the formula 4, I 004 represents the area integral value of the peak representing the (004) crystal plane in X-ray diffraction (XRD) spectroscopic analysis of the negative electrode active layer, I 110 The wound electrode assembly according to claim 1 , wherein m represents an area integral value of a peak indicating a (110) crystal plane in X-ray diffraction (XRD) spectroscopy analysis of the negative electrode active layer.

3. The alignment degree (O.I) of the first negative electrode active layer 1st ) is 0.1 to 2.0, The alignment degree (O.I) of the second negative electrode active layer 2nd ) is the alignment degree (O.I) of the first negative electrode active layer. 1st 3. The wound electrode assembly according to claim 2, wherein the ratio of the surface area to the surface area is 101% to 150% based on the surface area.

4. The first negative electrode active layer has an alignment degree (O.I) at the outermost surface of the electrode assembly. 1st ) is the alignment degree (O.I) at the winding center of the electrode assembly 1st 3. The wound electrode assembly according to claim 2, wherein the ratio of the surface area of ​​the electrode to the surface area of ​​the winding is 101% to 150% based on the surface area of ​​the electrode.

5. The first negative electrode active layer has a ratio (I) of the intensity of the peak representing the (004) crystal plane to the intensity of the peak representing the (002) crystal plane when measured by XRD using CuKα radiation. 004 / I 002 2. The winding type electrode assembly according to claim 1, wherein the value of (a) is 0.04 or more.

6. The wound electrode assembly according to claim 1 , wherein the carbon-based negative electrode active material comprises at least one of natural graphite and artificial graphite.

7. 2. The wound electrode assembly according to claim 1, wherein the carbon-based negative electrode active material has a sphericity of 0.75 or more.

8. The first negative electrode active layer and the second negative electrode active layer each have a thickness of 250 mg / 25 cm 2 ~500mg / 25cm 2 2. The wound electrode assembly according to claim 1, having a loading amount of

9. The positive electrode includes a positive electrode active layer provided on both sides of a positive electrode current collector, and the positive electrode active layer includes at least one positive electrode active material selected from lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2: [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O 2 [Chemical formula 2] LiM 2 p Mn 1-p O 4 In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are each in the range of 1.0≦x≦1.30, 0.5≦y<1, 0<z≦0.3, 0<w≦0.3, 0≦v≦0.1, and y+z+w+v=1; M 2 is Ni, Co or Fe, 2. The wound electrode assembly according to claim 1, wherein p satisfies the condition 0.05≦p≦1.

0.

10. The positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 , LiNi 0.6 Co 0.2 Mn 0.2 O 2 , LiNi 0.9 Co 0.05 Mn 0.05 O 2 , LiNi 0.6 Co 0.2 Mn 0.1 A 0.1 O 2 , LiNi 0.6 Co 0.2 Mn 0.15 A 0.05 O 2、 LiNi 0.7 Co 0.1 Mn 0.1 A 0.1 O 2 , LiNi 0.7 Mn 1.3 O 4 , LiNi 0.5 Mn 1.5 O 4 , LiNi 0.3 Mn 1.7 O 4 , LiFePO 4 , LiFe 0.8 Mn 0.2 P.O. 4 , and LiFe 0.5 Mn 0.5 P.O. 4 The wound electrode assembly of claim 9, comprising one or more of the following:

11. A lithium secondary battery comprising the wound-type electrode assembly according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Negative electrode piece, preparation method thereof and lithium ion battery

    CN114005957A

  • Battery, negative electrode for battery, battery pack, electronic apparatus, electric vehicle, power storage device and power system

    JP2013211228A

  • Electrode assembly and rechargeable battery including the same

    US20190355972A1

  • Modified natural graphite particles

    WO2012137770A1

  • KR20210039599A